2018
DOI: 10.1136/bmjopen-2017-019662
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of cigarette pack inserts promoting cessation and dissuasive cigarettes among young adult smokers in the UK: a cross-sectional online survey

Abstract: ObjectivesTo explore young adult smokers’ perceptions of cigarette pack inserts promoting cessation and cigarettes designed to be dissuasive.DesignCross-sectional online survey.SettingUK.ParticipantsThe final sample was 1766 young adult smokers, with 50.3% male and 71.6% white British. To meet the inclusion criteria, participants had to be 16–34 years old and smoke factory-made cigarettes.Primary and secondary outcome measuresSalience of inserts, perceptions of inserts as information provision, perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…stubbing cigarettes out early or reducing consumption), encourage or lead to quitting, or deter young people, nonsmokers and those starting to smoke. This adds to online surveys which found that the warning 'Smoking kills' on cigarettes, in comparison to regular cigarettes, were associated with a lower likelihood of perceived trial (Lund and Scheffels 2018;Moodie, Hiscock et al 2018;Moodie et al 2019), and an in-home survey in which more than half of participants thought that having this warning on cigarettes would encourage cessation and almost three-quarters that it would discourage initiation (Moodie et al 2017). These studies, collectively, suggest that warnings on cigarettes may have the potential to impact the decisions of people to start, continue or stop smoking, contrary to tobacco companies claims that there is no evidence to suggest that this would be the case (Nuthall 2019).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…stubbing cigarettes out early or reducing consumption), encourage or lead to quitting, or deter young people, nonsmokers and those starting to smoke. This adds to online surveys which found that the warning 'Smoking kills' on cigarettes, in comparison to regular cigarettes, were associated with a lower likelihood of perceived trial (Lund and Scheffels 2018;Moodie, Hiscock et al 2018;Moodie et al 2019), and an in-home survey in which more than half of participants thought that having this warning on cigarettes would encourage cessation and almost three-quarters that it would discourage initiation (Moodie et al 2017). These studies, collectively, suggest that warnings on cigarettes may have the potential to impact the decisions of people to start, continue or stop smoking, contrary to tobacco companies claims that there is no evidence to suggest that this would be the case (Nuthall 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Twenty focus groups were conducted between January-March 2015 with 120 smokers in the two most populated cities in Scotland (Glasgow, Edinburgh) to explore their perceptions of cigarette packaging, pack inserts promoting cessation (Moodie 2018b ), and also cigarette design, which is the focus of this paper. Focus groups were employed as they are helpful for gaining insight into how a particular sample may respond to a novel concept, in this case how smokers respond to cigarettes with the warning ‘Smoking kills’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7] Much of this research has been led by researchers in New Zealand, [8][9][10][11][12] but further research has also been conducted in Norway 4 and the United Kingdom. 13 There are several means to portray cigarettes as repellent, including proposals to remove additives such as sugar and menthol, ensuring that cigarettes taste bitter and far less palatable to smokers. However, the current leading proposals designed to modify cigarettes to create 'dissuasive sticks' focus on two key areas.…”
mentioning
confidence: 99%